2005
DOI: 10.1073/pnas.0508234102
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome exit tunnel can entropically stabilize α-helices

Abstract: Several experiments have suggested that newly synthesized polypeptide chains can adopt helical structures deep within the ribosome exit tunnel. We hypothesize that confinement in the roughly cylindrical tunnel can entropically stabilize ␣-helices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
128
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 33 publications
5
128
2
1
Order By: Relevance
“…Simulations using spheres as confinement do not qualitatively change the results with respect to the cases using spherical cylinders (10,22,23). Although study using an infinite cylinder shows different effects of the confinement on folding (21), this kind of confinement is different from those using spheres or spherical cylinders due to the absence of restriction along the axis. Furthermore, a study on the molecular crowding effect on folding of globular proteins suggested that, to depict a rather crowded in vivo environment, the optimal cavity to host protein molecule may be cylindrical (11).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Simulations using spheres as confinement do not qualitatively change the results with respect to the cases using spherical cylinders (10,22,23). Although study using an infinite cylinder shows different effects of the confinement on folding (21), this kind of confinement is different from those using spheres or spherical cylinders due to the absence of restriction along the axis. Furthermore, a study on the molecular crowding effect on folding of globular proteins suggested that, to depict a rather crowded in vivo environment, the optimal cavity to host protein molecule may be cylindrical (11).…”
Section: Resultsmentioning
confidence: 80%
“…Other shapes, such as a sphere or an infinite cylinder, were also used previously to study the confinement/crowding effect on protein folding (10,11,13,(21)(22)(23). Simulations using spheres as confinement do not qualitatively change the results with respect to the cases using spherical cylinders (10,22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Confinement has been previously treated both analytically and via simulation using polymer physics models (3)(4)(5)(6)(7)(8)(9)(10). These models predict that by excluding more extended structures confinement reduces the conformational entropy of the unfoldedstate ensemble.…”
mentioning
confidence: 99%
“…Specifically, Ziv et al (10) have suggested that for a small helical peptide helix formation is stabilized upon confinement to a cylindrical cavity. These results were explained in terms of polymer entropy arguments as described above.…”
mentioning
confidence: 99%
“…However, further results of biochemical, microscopical and computational experiments clearly showed that this tunnel participates actively in nascent chain progression, arrest and cellular signalling (e.g. Gabashvili et al 2001;Gong & Yanofsky 2002;Nakatogawa & Ito 2002;Berisio et al 2003Berisio et al , 2006Gilbert et al 2004;Johnson & Jensen 2004;Woolhead et al 2004Woolhead et al , 2006Amit et al 2005;Ziv et al 2005;Cruz-Vera et al 2006;Kaiser et al 2006;Mankin 2006;Mitra et al 2006;Tenson & Mankin 2006;Voss et al 2006;Deane et al 2007;Schaffitzel & Ban 2007;Petrone et al 2008), and that in eubacteria, nascent proteins progress along this tunnel and emerge into a shelter formed by chaperones, preventing aggregation and misfolding Schluenzen et al 2005).…”
Section: Introductionmentioning
confidence: 99%